Modal Synthesis of the Controller of the Underwater Vehicle Motion Control System - Ezangina T. A. Tatiana Aleksandrovna (2024, 2024)
The paper is dedicated to developing a method of maximizing a degree of robust stability of control systems with interval parameters based on a method of mathematical programming and root locus theory. The research resulted in a method of synthesizing a robust controller providing maximal operating speed of interval control systems in the worst operating modes. To prove effectiveness of the method proposed a controller for motion control system of an unmanned underwater vehicle with interval parameters was synthesized. Control quality of the system synthesized was examined with the help of multiparametric interval root locus